Propuesta de programa de gobierno de datos para la empresa de Prestación de Servicios Temporales (2022)
This project presents the approach of the data governance program of the Provision of Temporary Services company that is defined from the identification of a data management and quality problem that prevents the continuation of the normal execution of the initiatives of its program of digital transformation